Structural Study in the Arabic Linguistic Heritage: The Phenomenon of the Grammatical Context as a Case Study" - soltani, farouk (El Omda in Linguistics and Discourse Analysis, 2018)
Ancient linguists paid significant attention to linguistics, addressing numerous and diverse topics and themes that are valuable for linguistic structure within discourse. The syntactic level is an integral part of this rich and esteemed linguistic heritage, where syntax serves as a hub for phonetic, morphological, and grammatical relationships through which meaning is determined. The grammatical context (al-qareena al-nahwiyya) is one of the most important topics examined by early linguists in the Arabic linguistic tradition. They studied its types and categories, demonstrating that the grammatical context plays a crucial role in producing meaning within syntactic structures.